THE CAUSATIVE FACTOR DETECTION AND IDENTIFICATION OF BOOPHILUS SP. INFESTATION IN BALI CATTLE IN BARRU REGENCY, SOUTH SULAWESI - Suparmin Yuliani; Risha Catra Pradhany; Faizal Zakariya (Buletin Veteriner Udayana, 2024)
In tropical climates such as Indonesia, the presence of ectoparasites occurs almost annually, which becomes one of the major problems due to ectoparasite infestations on ruminant farms. One problem occurred is the Boophilus sp. This study aimed to detect and identify causative factor in infestation of Boophilus sp. and correlation between tick infestation and incidence of blood parasite in Barru Regency. The study unit was the Bali cattle breeders spreaded in Mallusetasi District, Barru Regency. This study used a cross-sectional study to identify and determine the relationship between the causative factors of maintenance management and stock farmer knowledge level on the application of maintenance management in Bali cattle farms. The tabulated data of the maintenance management in Bali cattle breeding and breeder knowledge level causative factors against the tick ectoparasite infestation were descriptively analyzed and tested with a chi-square (χ2) method to measure the relationship of these factors and Boophilus sp. tick infestation at 95% of confidence level. The magnitude of relationship strength was calculated by the odd ratio (OR) test at a 95% of confidence level. Boophilus sp. tick ectoparasite infestation occurred in Bali cattle farms in Mallusetasi District, Barru Regency with an incidence rate of 68,8%. The causative factors that influence the incidence of tick infestations included the farmer educational level, breeder experience, number of maintenance, maintenance pattern, poor cage condition, and breeder's knowledge. The infestation of Boophilus sp. tick had a very significant correlation on the incidence of blood parasitic diseases. Therefore, to reduce tick infestation and the incidence of blood parasitic disease, planning of integrated control measures to create awareness about the importance and control of tick for livestock farmers is required.